Conscience the Path to Holiness : Walking with Newman. - Miller, Edward Jeremy (Cambridge Scholars Publishing, 2014)
The writings on the nature of conscience are many, and those of John Henry Cardinal Newman about conscience are among the very best. Conscience the Path to Holiness: Walking with Newman is the work of ten Newman scholars from three continents. Against the contemporary view that conscience means one's inalienable right to assert with impunity whatever one feels personally convinced of, this book reclaims a richer and more balanced presentation of conscience that avoids what Newman, in his day ...